PERSEPSI PERTUKARAN SOSIAL MEMEDIASI HUBUNGAN ANTARA PERSEPSI POLITIK ORGANISASI DAN KEPUASAN KERJA MAHASISWA PROGRAM MASTER PADA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA - Masrurah, Murkhana (Departemen Manajemen, 2017)
This study aims to investigate the influence of social exchange perception that mediate the relationship between perceptions of organizational politics and job satisfaction. The sample used in this study were the students Master Program of Economics and Business Faculty of Syiah Kuala University. This research method using questionnaire as a research instrument. Probability random sampling was used as the sampling technique. The method of analysis Hierarchical Linear Modeling (HLM) is used as a method of analysis to determine the effect of the variables involved. The results of this study showed that perceptions of organizational politics influence on job satisfaction, perceptions of organizational politics influence not significant the perceptions of social exchange, social exchange perceptions effect on job satisfaction. Additionally result that social exchange perceptions not mediates the influence on perceptions of organizational politics and job satisfaction at the students Master Program of Economics and Business Faculty of Syiah Kuala University. Keywords: Job Satisfaction, Perceptions of Organizational Politics, Social Exchange Perceptions